UPAYA MENINGKATKAN HASIL BELAJAR PASSING BAWAH BOLA VOLI MELALUI VARIASI PEMBELAJARAN - Jamaiah, Jamaiah; Triansyah, Andika; Puspa, Fitriana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is the understanding of basic passing under the material can not dikuasi well is to know the improvement of passing learning outcomes under melalaui direct learning model assisted media on the fourth grade students of Elementary School 3 Gandis Hilir. In accordance with research objectives, then this research using the type of research